Left Ventricular Torsion Shear Angle Volume Approach for Noninvasive Evaluation of Diastolic Dysfunction in Preserved Ejection Fraction. Issue 1 (29th December 2017) - Sharifov, Oleg F.; Schiros, Chun G.; Aban, Inmaculada; Perry, Gilbert J.; Dell'italia, Louis J.; Lloyd, Steven G.; Denney, Thomas S.; Gupta, Himanshu
Abstract : Background: Accurate noninvasive diagnostic tools for evaluating left ventricular (LV) diastolic dysfunction (LVDD) are limited in preserved LV ejection fraction. We previously proposed the relationship of normalized rate of change in LV torsion shear angle (φ′) to corresponding rate of change in LV volume (V′) during early diastole (represented as −dφ′/dV′) as a measure of LV diastolic function. We prospectively evaluated diagnostic accuracy of −dφ′/dV′ in respect to invasive LV parameters. Methods and Results: Participants (n=36, age 61±7 years) with LV ejection fraction ≥50% and no acute myocardial infarction undergoing coronary angiography for chest pain and/or dyspnea evaluation were studied. High‐fidelity invasive LV pressure measurements and cardiac magnetic resonance imaging with tissue tagging were performed. τ, the time constant of LV diastolic relaxation, was 58±10 milliseconds (mean±SD), and LV end‐diastolic pressure was 14.5±5.5 mm Hg. Cardiac magnetic resonance imaging‐derived −dφ′/dV′ was 5.6±3.7. The value of −dφ′/dV′ correlated with both τ and LV end‐diastolic pressure ( r =0.39 and 0.36, respectively, P <0.05). LVDD was defined as τ>48 milliseconds and LV end‐diastolic pressure >12 mm Hg (LVDD1), or, alternatively, τ>48 milliseconds and LV end‐diastolic pressure >16 mm Hg (LVDD2). Area under the curve (AUC) of −dφ′/dV′ for identifying LVDD1 was 0.83 (0.67‐0.98, P =0.001), with sensitivity/specificity of 72%/100% for −dφ′/dV′ ≥6.2. AUC of −dφ′/dV′ for identifying LVDD_2 was 0.82 (0.64‐1.00, P =0.006), with sensitivity/specificity of 76%/85% for −dφ′/dV′ ≥6.9. There were good limits of agreement between pre‐ and post‐nitroglycerin −dφ′/dV′. Conclusions: The −dφ′/dV′ obtained from the LV torsion volume loop is a promising parameter for assessing global LVDD with preserved LV ejection fraction and requires further evaluation.